Development of A Chemistry E-Module Based on Project Based Learning Using the Flipbook Application to Improve Learning Outcomes and Train Collaboration on Acid Base Material - Hany, Nadila Cempaka; Syafriani, Dewi (UNDIKMA, 2024)
This research aims to: (1) determine the validity of PjBL-based e-modules, (2) determine the practicality of PjBL-based e-modules, (3) determine the effectiveness of PjBL-based e-modules, and (4) determine whether there is a significant correlation between collaboration and learning outcomes. This research was conducted at SMA Negeri 1 Stabat with the sample studied being class Data analysis techniques were carried out by: e-module feasibility test according to BSNP, collaboration skills test, and correlation test between collaboration skills and learning outcomes. The results obtained in this research are: (1) The PjBL-based E-module is said to be